Belt and Road Initiative as a Tool for the International Socialization of Political Elites - A. S. Zaseeva; M. I. Ivanova; G. P. Galin (Vestnik MGIMO-Universiteta, 2022)
Book review: Tudoroiu T., Ramlogan А. 2021. China’s International Socialization of Political Elites in the Belt and Road Initiative. Routledge. 292 p.